A project feasibility study guidebook for Filipino students ... & entrepreneurs; foreword by Melito S. Salazar, Jr. - Cuyugan, Jorge Henson (A business planning manual, 1993)
"The authors' objective in writing this work is to cut the students' field researches to a considerable degree but at the same time force them to think (and not just copy) what to write as what is detailed are choices and instructions. Part I discusses the basic of Project Study research writing and contains an introduction to different feasibility studies. It also contains a reproduction of the latest Philippine Investments Priorities Plan that should be helpful to the students in determining their topic of interest for their study. It also has a detailed information list of both government and private Information/ centers as supplemetal guides. Part II is a "beginners' manual" for project feasibility study preparation. It starts with a proposed general format on which the students could use for individual researches and considering the practicality of its contents' details, could be used also by entrepreneurs on their studies for actual implementation."--Preface.